2002
DOI: 10.1046/j.1365-2249.2002.01685.x
|View full text |Cite
|
Sign up to set email alerts
|

IL-1ra and IL-1 production in human oral mucosal epithelial cells in culture: differential modulation by TGF-β1 and IL-4

Abstract: SUMMARYRegulatory cytokines mediate the participation of oral mucosal epithelial cells (OMEC) in local immune responses. The aim of this study was to characterize the isoforms of IL-1 receptor antagonist (IL-1ra) in cultured human primary OMECs and to compare its production with that of IL-1 alpha (IL-1a ) and IL-1 beta . Western blot analysis showed that IL-1ra was 22 kDa in size hence slightly smaller than monocyte IL-1ra (25 kDa). A minor form of 20 kDa was also found in unstimulated cell culture lysates. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
1
14
0
1
Order By: Relevance
“…26 Using RT-PCR or cDNA microarray, IL-1ra has been found to be expressed by human amniotic cells 46 and significantly upregulated in limbal epithelial cells expanded on intact human amniotic membrane. 47 Expression of IL-1ra in oral mucosa also has been reported, 27 but we found only weak staining in the basal layer of oral mucosal epithelia. However, IL-1ra was expressed abundantly by the OMECs in the corneal specimens, especially in the basal epithelium, which presumably contains the stem cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…26 Using RT-PCR or cDNA microarray, IL-1ra has been found to be expressed by human amniotic cells 46 and significantly upregulated in limbal epithelial cells expanded on intact human amniotic membrane. 47 Expression of IL-1ra in oral mucosa also has been reported, 27 but we found only weak staining in the basal layer of oral mucosal epithelia. However, IL-1ra was expressed abundantly by the OMECs in the corneal specimens, especially in the basal epithelium, which presumably contains the stem cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Finally, to explain the late onset (3-6 months) and limited corneal NV after COMET, [13][14][15][16] we chose to study the expression of IL-1ra, which previously was found to be expressed constitutively in the human cornea 26 or cultivated OMECs, 27 and has been shown to inhibit corneal NV in mice. 28 Signaling for IL-1ra was positive strongly in the normal corneal epithelium, but only mildly positive in normal conjunctival and oral mucosal epithelia.…”
Section: Expression Of Anti-inflammatory Factorsmentioning
confidence: 99%
“…Cells known to secrete IL‐1ra include immune cells [9–11], epithelial cells [12,13] skin keratinocytes [14], stromal cells [15–18], hepatocytes [19] and adipocytes [20].…”
Section: Il‐1ramentioning
confidence: 99%
“…The differential response to spent vs. fresh pGIFU and GIFU media observed for levels of IL1ra and G-CSF could signify suppression of these cytokines by factors present in the pro-in ammatory bacterial cultures. IL1ra has been demonstrated to be produced at elevated levels at the apical surface of cervical epithelium [63], and at biologically relevant (with respect to modulating IL1β) levels by oral mucosal epithelium [64]. IL1ra plays the important role of inhibiting the effect of pro-in ammatory IL1β by binding to its receptor, and its modulation by microbial factors has been associated with reduced intestinal in ammation and tissue damage [65,66].…”
Section: Discussionmentioning
confidence: 99%